2008
DOI: 10.1007/s00267-008-9137-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Farmers’ Adoption of Improved Soil Conservation Technology in a Middle Mountain Watershed of Central Nepal

Abstract: This study explores different socio-economic and institutional factors influencing the adoption of improved soil conservation technology (ISCT) on Bari land (Rainfed outward sloping terraces) in the Middle Mountain region of Central Nepal. Structured questionnaire survey and focus group discussion methods were applied to collect the necessary information from farm households. The logistic regression model predicted seven factors influencing the adoption of improved soil conservation technology in the study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
61
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 25 publications
18
61
3
1
Order By: Relevance
“…This result is consistent with studies reported by Genius et al (2006). However, our result is contradicting with observations made by Tiwari et al (2008);Mendola (2007). Hence, the impact of farmers' age on extension participation and/or technological adoption is ambiguous as expected.…”
Section: Determinants Of Extension Program Participationcontrasting
confidence: 57%
“…This result is consistent with studies reported by Genius et al (2006). However, our result is contradicting with observations made by Tiwari et al (2008);Mendola (2007). Hence, the impact of farmers' age on extension participation and/or technological adoption is ambiguous as expected.…”
Section: Determinants Of Extension Program Participationcontrasting
confidence: 57%
“…A study in Nepal revealed four primary motivating factors for adoption of improved soil conservation technologies like CC/GM (Fig. 5) : neighbor experiences (35%), multifunctionality (30%), finance and material support (20%), and training and extension (15%) [58]. Furthermore, farmer surveys in the Kaski and Dhading districts of Nepal indicate that their terrace land is too dry to grow most crops including many leguminous CC/ GM in the dry season [7].…”
Section: Limitations To the Adoption Of Sustainable Agriculture Intermentioning
confidence: 99%
“…The potential for crop failure is exacerbated by the reliance on a few plant species [5,6,61,62]. Plant species vary in their vulnerabilities and resistances to hazards like environmental stress including heat, cold, drought, floods, pests, [58] and disease. As a result, the reliance on a few crop species is a risk for farmers [62].…”
Section: The Need To Diversify Crop Species To Adapt To a Changing Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the study results can be used to develop a more efficient on-farm plantation forestry adoption strategy. This is important given the fact that 22.8 percent of rural households in Uganda still suffer from absolute poverty (Ministry of Finance, Planning and Economic Development [MFPED], 2014) Several studies have assessed the factors influencing adoption of farm forestry in developing countries (Adesina et al, 2000;Oeba et al, 2012;Tiwari et al, 2008;Bayard et al, 2007). These studies reported that adoption was influenced by demographic, socio-economic, institutional and farm characteristics such as contact with extension agencies, belonging to farmer's groups, population pressure, fuel wood scarcity, tree tenure security, size of land holding, education level, soil erosion index and gender.…”
Section: Introductionmentioning
confidence: 99%